Education Through Participation (EAAE Annual Conference Proceedings, 2019)
The word ‘education’ is defined to be: ‘the process of receiving or giving systematic instruction, especially at a school or university’ by the Cambridge Dictionary. And this is supposedly the definition of what we do at the MSA as well as every other university. Except there is that other layer of learning that weaves its importance into the fabric of our everyday educational experience.The participation model of students at the MSA is exemplary in the German higher education landscape, as the student body takes an important place in responsibility and organization of the Münster School of Architecture. It is thanks to active student involvement in important tasks, faculty policy decisions and representation of the school, that it is a distinguish part of the MSA.
Keywords: students; change; participation; engagement; interaction